PENGEMBANGAN VIDEO ANIMASI BERBASIS POWTOON MATERI GAYA DALAM MENINGKATKAN HASIL BELAJAR IPA SISWA SD - Putri Rahadian Dyah Kusumawati; Anggi Aprilliantika (PendIPA Journal of Science Education, 2022)
The goal of this study was to develop a Powtoon animated video on Force material. The subjects of this study were fourth-grade students at elementary school SDN Kendaga Larangan Brebes. This research used the ADDIE (Analyze, Design, Development, Implementation, and Evaluation) development model. The methods of data collection used were tests for the students. Data were analyzed with a quantitative descriptive approach. Animated video meets validation by material experts in the proper category and media experts in the feasible category. Animated videos are also effective in improving students' science learning outcomes.